1973
DOI: 10.1021/j100629a007
|View full text |Cite
|
Sign up to set email alerts
|

Pulse radiolytic study of the site of hydroxyl radical attack on aliphatic alcohols in aqueous solution

Abstract: The formation of reducing and oxidizing radicals has been investigated in the reaction of hydroxyl radicals with formate, alcohols, and diols in pulse-irradiated aqueous solutions. Reducing radicals (C02~a nd a-alcohol radicals) were identified by their reaction with tetranitromethane, oxidizing alkoxy radicals by their reaction with iodide. The reaction of hydroxyl radicals with formate and ethylene glycol exclusively leads to a radical with reducing properties. The principal reducing radical from methanol, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
258
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(268 citation statements)
references
References 3 publications
10
258
0
Order By: Relevance
“…Consistent ratios of 0:5:6:1:1:1:1 were found for the six stable alkoxyamine product peaks observed (Fig. 7) This differs from the ratios of the number of protons on each carbon (2:2:2:2:2:2:3) because all of the protons are not extracted with equal efficiency as has been seen previously (Asmus et al, 1973). As this is a region of changing HPLC gradient, the varying quantum yields of the alkoxyamines in different solvents effect the peak ratios (although by no more than a factor of two) (see Chapter 1, Table I.…”
Section: Octanol As Primary Trapsupporting
confidence: 74%
See 1 more Smart Citation
“…Consistent ratios of 0:5:6:1:1:1:1 were found for the six stable alkoxyamine product peaks observed (Fig. 7) This differs from the ratios of the number of protons on each carbon (2:2:2:2:2:2:3) because all of the protons are not extracted with equal efficiency as has been seen previously (Asmus et al, 1973). As this is a region of changing HPLC gradient, the varying quantum yields of the alkoxyamines in different solvents effect the peak ratios (although by no more than a factor of two) (see Chapter 1, Table I.…”
Section: Octanol As Primary Trapsupporting
confidence: 74%
“…Hydroxyl radical reacts with t-butanol (16) both by extracting a proton from one of the methyl groups (95.7%) and by extracting the proton from the alcohol which rearranges to generate a methyl radical (4.3%) (Asmus et al, 1973). These radicals are trapped by 3-amp and elute at around 18.5 and 19 minutes, respectively, and in the expected ratio.…”
Section: T-butanol As Primary Trapmentioning
confidence: 99%
“…The fact that a product isotope effect is measurable may indicate that the perturbation by 1-propanol is through insertion between the hydrophobic sites of helix I and helix IV bringing 1-propanol sufficiently close to the yet perturbed metal-binding site to scavenge reactive oxygen species. Three experimental facts would support an assignment that this reactive species is either a hydroxyl radical or a metal-bound equivalent, a complexed hydroxyl radical: (i) the anaerobic reaction of hydrogen peroxide with a hGH-Cu(I) complex, most likely [hGHCu(I)] mbs , is expected to proceed according to Equations 12 and 13 (44 (ii) The most reactive C-H bonds of 1-propanol are the respective C ␣ -H bonds (45). Pulse radiolytic studies have shown that the primary kinetic isotope effect for the reaction of the hydroxyl radical with the C ␣ -H and the C ␣ -D bonds of methanol-h 3 and methanol-d 3 , respectively, is on the order of k H /k D ϭ 2.25 (46), i.e.…”
Section: The Effect Of 1-propanolmentioning
confidence: 67%
“…Here, an acetone radical anion is formed which should promptly be protonated giving a strongly reducing alkyl radical (CH 3 ) 2 C • (OH), the same as generated via reaction (4) with 86% yield. 44 The fate of the holes generated in this system is unclear, but at least recombination of holes and electrons is suppressed. One can propose that the holes could be transformed first into hydroxyl radicals (3), which further react with acetone via H-abstraction (see eqn (S1), ESI †) with a rate constant of k = 1.3 × 10 8 dm 3 mol −1 s −1 ).…”
Section: Resultsmentioning
confidence: 99%